2012
DOI: 10.1103/physrevlett.108.075502
|View full text |Cite
|
Sign up to set email alerts
|

Direct Insight into Grain Boundary Reconstruction in PolycrystallineCu(In,Ga)Se2with Atomic Resolution

Abstract: This work presents results from high-resolution scanning transmission electron microscopy and electron energy-loss spectroscopy on twin boundaries (TBs) and nontwin grain boundaries (GBs) in CuðIn; GaÞSe 2 thin films. It is shown that the atomic reconstruction is different for different symmetries of the grain boundaries. We are able to confirm the model proposed by Persson and Zunger [Phys. Rev. Lett. 91, 266401 (2003)] for Se-Se-terminated AE3 f112g TBs, showing Cu depletion and In enrichment in the two ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 32 publications
9
55
1
Order By: Relevance
“…In previous studies, the occurrence of cation redistribution at random GBs was unambiguously demonstrated, including clear evidence for regions with Cu enrichment and In depletion. 16,17 However, contrary to the present report, these Cu-rich/In-poor boundary regions did not exhibit any clear crystallinity, i.e., no highly ordered secondary phase was observed at those boundaries. The presence of a remnant Cu 2-x Se fully ordered phase at GBs and within grains appears therefore to be a rare occurrence (within the limited statistics of atomic-resolution STEM observation).…”
contrasting
confidence: 55%
“…In previous studies, the occurrence of cation redistribution at random GBs was unambiguously demonstrated, including clear evidence for regions with Cu enrichment and In depletion. 16,17 However, contrary to the present report, these Cu-rich/In-poor boundary regions did not exhibit any clear crystallinity, i.e., no highly ordered secondary phase was observed at those boundaries. The presence of a remnant Cu 2-x Se fully ordered phase at GBs and within grains appears therefore to be a rare occurrence (within the limited statistics of atomic-resolution STEM observation).…”
contrasting
confidence: 55%
“…S3 in SM 22 ). Due to a reduced density at GBs, 27,28 grain growth, i.e. reduction of GB area, generally leads to a material densication.…”
Section: B Correlation Between Strain Relaxation and Grain Growthmentioning
confidence: 99%
“…When soda-lime glass is used as substrates, even further point defects related to impurities such as Na, O, and K, which diffuse from the glass substrate into the Cu(In,Ga) Se 2 thin films, contribute to the grain-boundary compositions. 35 The complex scenario of the compositional and optoelectronic properties of random grain boundaries in Cu(In,Ga)Se 2 thin films is difficult to be translated into a corresponding energy-band diagram and eventually into a two-or three-dimensional device simulation, which ultimately would give direct insight into how (random) grain bound- aries affect the device performance. Corresponding work is currently in progress.…”
Section: Ebsd Combined With Other Scanning Microscopy Techniquesmentioning
confidence: 99%
“…Indeed, compositional changes are found in Cu(In,Ga)Se 2 thin films within regions around random grain boundaries that have widths of smaller than 1 nm. 34 This is, the atomic planes of neighboring grains that meet at random grain boundaries in Cu(In,Ga)Se 2 thin films are considered reconstructed. It has been found 34,35 that the changes in composition and thus the reconstruction is always different for different (random) grain boundaries, even in identical Cu(In,Ga)Se 2 thin films.…”
Section: Ebsd Combined With Other Scanning Microscopy Techniquesmentioning
confidence: 99%